DINAMIKA PENEGAKAN HUKUM DAN KOMISI PEMBERANTASAN KORUPSI YANG TEGAS, CEPAT, DAN TANGGAP DALAM PEMBERANTASAN KORUPSI TAHUN 2025 - KADEK FREDIANDRIKA ADNANTARA (Fakultas Hukum Universitas Ngurah Rai, 2025)
Corruption is one of the biggest challenges in building good governance in Indonesia. The Corruption Eradication Commission (KPK) as an independent institution is required to be firmer, faster, and more responsive in dealing with increasingly complex corruption cases. The dynamics of law enforcement by the KPK in 2025 reflect multidimensional challenges, including political pressure, limited resources, and the development of corruption modus operandi. the KPK’s strategy in eradicating corruption and the obstacles it faces, as well as providing solutions to strengthen the integrity and effectiveness of this institution. The research method used is juridical, namely through the use of laws, norms or symphonies of Dassault and social and cultural reality. The results of the study show that law enforcement must be firm, fast and responsive to the eradication of corruption in 2025